ANALISIS PENERAPAN DALUWARSA DALAM PENGAJUAN GUGATAN TERHADAP HAK UNTUK MEMPEROLEH PEKERJAAN BAGI PENYANDANG DISABILITAS DALAM SISTEM PEREKRUTAN PEGAWAI NEGERI SIPIL (STUDI PUTUSAN NOMOR 85/G/2020/PTUN.SMG) - Felishella Earlene; Tatang Ruchimat (Jurnal Hukum Adigama, 2021)
Everyone who feel their interests are harmed due to the issuance of a State Administrative Decree has the right to file a lawsuit into authorized State Administrative Court. In the filling of a lawsuit, there are expiration provisions that are regulated in the applicable regulations. If the lawsuit is filed beyond the expiration date, then the lawsuit cannot be accepted, on the other side there is interests of a person that have been harmed. How is the legal protection for the loss of rights to obtain employment for person with disabilities in the civil servant recruitment system due to the implementation of expiration in filling lawsuit? In this research, the Author uses normative research method. The result of this research is the implementation of expiration provisions in filling a lawsuit provides legal certainty, but on the other side provides limitations for them who feel that their interests have been harmed so the justice cannot be reached. Judge in examining and passing verdicts should be based on the applicable regulations by balancing between legal certainty and justice for the seeker of justice. Therefore, the legal protection that can be provided to the rights of person with disabilities who are lost because the lawsuit filed has expired is to ensured that person with disabilities can participate in selection in the following year without discriminatory treatment. It is better if everyone who files a lawsuit on State Administration pays more attention towards the expired provisions so that similar problems do not occur.